A voz feminina na literatura de ascendência africana: hibridismo de mitos e ritos nos romances Niketche de Paulina Chiziane e A cor púrpura de Alice Walker - Santos, Waltecy Alves dos (2009)
This paper associates Literary Studies to Cultural Studies with the intention of comparing literatures that show itself as historically constituted subjects. In this sense, The female voice in literature of African ascendency: hybridism of myths and rites in the novels Niketche of Paulina Chiziane and The Color Purple of Alice Walker is a study that suggest literary-cultural reflections on the constructions of identities in these works. The research focuses on the construction of the subject through his speech and establishing the relationship with remarkable images in search of otherness namely, the mirror, unfolded in the letter, and the bed in addition to pointing out the problem of myths and rites as matrices to a new voice defined by cultural hybridism and fixed in orality. Finally, this research tries to describe the similarities and differences with respect to oppression and exclusion of marginal voices in case of the female voice of African ascendency examining them in what they have of challenging and transgressive in front of eurocentrical, patriarchal and theological assumptions, as they are presented in these works